Storage Stability of Turkey Meat Sausage incorporated with Carrot and Radish under Refrigerated Storage: 10.5958/2581-6616.2020.00019.5 - Reddy, M. Naveen Kumar; Kumar, M. Shashi; Reddy, G.V. Bhaskar; Krishnaiah , N.; Reddy , N. Anitha (Journal of Meat Science, 2020)
The present study was aimed to evaluate the antioxidant and antimicrobial efficacy of raw carrot paste (RCP) and raw radish paste (RRP)each at 10 % level on aerobic packaged turkey meat sausages under refrigeration (4±1°C) for a period of 25 days. The stored sausages were evaluated for physico-chemical, microbiological and sensory characteristics at an interval of 5 days. The pH of the turkey meat sausages increased significantly (P
Keywords: Turkey meat sausages; Carrot Paste; Radish paste; Aerobic package; Refrigeration